TCDD Attenuates EAE Through Induction of FasL on B Cells and Inhibition of IgG Production - Kummari, Evangel (Toxicology, 2020)
Previously we demonstrated that 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) suppressed experimental autoimmune encephalomyelitis (EAE), a model to study multiple sclerosis (MS), through induction of regulatory T cells (Tregs) and suppression of effector T cell function in the spleen. Since B cells and specifically regulatory B cells (Bregs) have been shown to be so critical in the pathology associated with EAE and MS, we wanted to determine whether TCDD could also induce Bregs. We specifically hypothesized that a Fas ligand (FasL)+ Breg population would be induced by TCDD in EAE thereby triggering apoptosis in Fas-expressing effector T cells as one mechanism to account for inhibition of T cell function by TCDD. TCDD (0.1–2.5 μg/kg/day administered orally for 12 days) modestly increased the percentage of FasL+ B cells in the spleen and spinal cord in TCDD-treated EAE mice. However, we did not detect significant increases in percentages of FasL+ B cells using TCDD in vitro in mouse splenocytes or human peripheral blood mononuclear cells (PBMCs). Part of the modest effect by TCDD was likely related to the localized expression of FasL; for instance, in the spleen, FasL was more highly expressed by IgM(hi)IgD(lo) marginal zone (MZ) B cells, but IgM(lo)IgD(hi) follicular (FO) B cells were more responsive to TCDD. Consistent with our observation of modest upregulation of FasL, we also observed modest changes in mitochondrial membrane potential in T cells co-cultured with isolated total B cells or IgM-depleted (i.e., FO-enriched) B cells from TCDD-treated EAE mice. These data suggest that while small microenvironments of apoptosis might be occurring in T cells in response to TCDD-treated B cells, it is not a major mechanism by which T cell function is compromised by TCDD in EAE. TCDD did robustly suppress IgG production systemically and in spleen and spinal cord B cells at end stage disease. Thus these studies show that TCDD’s primary effect on B cells in EAE is compromised IgG production but not FasL+ Breg induction.